Dapagliflozin and Sitagliptin Combination Therapy: An Overview of Clinical Utility in Type 2 Diabetes Mellitus with Multiple Cardiovascular Risk Factors - Ravikumar, L; Kiwalkar, Ravindra S; S, Ravindra H; Lokesh, Beerakayala; Dabhade, Dhammdeep (Cardiology and Cardiovascular Medicine, 2023)
Cardiovascular disease remains the leading cause of mortality in patients with diabetes. Control of multiple cardiovascular risk factors in patients with type 2 diabetes mellitus often leads to substantial reduction in adverse cardiovascular events. Newer antihyperglycemic agents at several randomized controlled trials have demonstrated their cardiovascular safety along with reduction in cardiovascular outcomes in type 2 diabetes mellitus with or without heart failure. Sodium-glucose cotransporter 2 inhibitors and dipeptidyl peptidase-4 inhibitors reported to have positive CV outcomes; especially, combination therapy with dapagliflozin and sitagliptin seem to be suitable therapeutic option. However, data upon the fixed-dose combination of these agents is limited. This review discusses the rationale and clinical utility of combination therapy with dapagliflozin and sitagliptin in improving glycemic control and reducing cardiovascular events in patients with type 2 diabetes mellitus with multiple cardiovascular risk factors.